PERBEDAAN PRODUKSI ASI PADA IBU POST PARTUM YANG DILAKUKAN TEHNIK ACUPRESSURE POINTS FOR LACTATION DAN TEHNIK BREAST CARE (DI BPM SRI WAHYUNI, S.ST SURABAYA) - Hamimatus Zainiyah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2018)
During pregnancy, the prolactin hormone from placenta increases but breast milk usually does has come out because it is still inhibited by high estrogen levels. On the second or third day of postpartum, estrogen and progesterone levels drop significantly, so the effect of prolactin is more dominant and secretion of breast milk begins. By breastfeeding earlier the secretion of breast milk gets smoother. Based on a preliminary study, 46.0% of post partum mothers experienced non-breast milk. This study aims to determine the differences in the production of breast milk in post partum mothers who performed acupressure techniques for lactation and breast care techniques. This research is a kind of research of quasy exsperimental design with non equivalent control group design. The samples were 7 post partum mothers that used acupressure techniques for lactation and 7 post partum mothers used breast care techniques from in February to March 2017. The sampling technique used was non probability sampling (consecutive sampling). From the statistic test of Independent T-Test indicates that α = 0.05 and P value 0.03 thus P Value<alpha (0.03 <0.05) so that H0 is rejected and Ha accepted there was a difference in breast milk production in post partum mothers performed acupressure and breast care techniques in the BPM Sri Wahyuni area, S.ST Surabaya. Midwives are able to socialize this acupressure technique to all post partum mothers, so that midwives can help secretion of breast milk production for post partum mothers with acupressure techniques with relatively cheaper costs